The new National Health Insurance policy in South Africa: Public perceptions and expectations. (2nd April 2016) - Setswe, Geoffrey; Witthuhn, Jacqueline; Muyanga, Samson; Nyasulu, Peter
Abstract: Introduction : South Africa has the highest HIV/AIDS incidence in the world. Health is one of the priority areas of the government of South Africa, owing to high disease burden and healthcare inequality. Although substantial improvements to healthcare services have been achieved since the fall of the apartheid system in 1994, much needs to be done. Recently, the South African government proposed a new national health insurance (NHI) plan, moving from a two-tier (private and public health care) system to a single-tier system (NHI) to alleviate the current healthcare disparities. One of the key ingredients to a successful healthcare reform is community participation in the policy formulation and implementation. In order to facilitate community engagement in the NHI policy implementation a study was conducted to understand public perception and expectations of the new NHI of South Africa. Methods : A cross-sectional survey was carried out among adults accessing health services in three provinces of South Africa. A two-stage systematic sampling design was employed to obtain data from a bigger impact evaluation study of knowledge, attitudes and perceptions of NHI among 900 adults. Mobile-phone-assisted personal interviews (MPAPIs) were used to collect and transmit data via a network to a data bank. Participants' responses with regard to their perceptions and expectations of the new NHI proposal were recorded based on the following response categories: strongly agreed, agreed, disagreed, and strongly disagreed. Data for all participants were graded and the percentage of correct answers for each category was computed. Results and conclusion : The study, reported here, revealed positive public perception and a high level of expectations. The factors which influenced positive perceptions on the public health sector were personal experience at a health service, family experiences, media reports and the experiences of close friends. The NHI, due to general public excitement, will face the challenge of having to deal with such high expectation from the public regarding transformation of the health workers in terms of competency and attitudes in providing health care services, improved cleanliness of clinics and hospitals as well as timely delivery of healthcare services.